Parental Experiences in the Management of Children with Syndromic Craniofacial Diagnoses in Malaysia - Chi Adam, Khairul Bariah; Hariri, Firdaus; Ab Murat, Norintan; Yin, Loh Meii; Amran, Muhammad NurHalim (IIUM Medical Journal Malaysia, 2021)
INTRODUCTION: Patients with syndromic craniofacial diagnoses (SCD) require coordinated overall management and remain a parental challenge. This study assessed the parental experience and psychological outcome, as well as the evaluation of professional and community support, received in Malaysia. MATERIAL AND METHODS: The Craniofacial Experiences Questionnaire (CFEQ) was used to assess parents of SCD children registered with the Combined Oro-Craniomaxillofacial Clinic in University Malaya Medical Centre, Kuala Lumpur. RESULTS: Thirty parents participated in this study with their children’s age ranged from 2 months to 14 years old diagnosed with Apert, Crouzon, and Pfeiffer syndromes, as well as other SCD such as Goldenhar, Pierre Robin, and Nager. The majority of parents felt anxious whenever their child underwent an operation despite having positive perceptions of the outcome. Most respondents did not see the condition as handicap although 6.7% of parents were embarrassed by their child’s appearance. The majority of the respondents were worried about the financial implication, had to be occasionally absent from work due to their child’s regular appointments, and felt depressed while only a quarter of respondents socialised less and struggled to meet parenting needs. Most respondents received positive comments, were treated with respect, and obtained adequate support from both health professionals and the community with regards to their childcare. CONCLUSIONS: Although most parents were concerned about their children’s condition, only minimal social stigmatisation was noted. Parents were satisfied with the emotional and physical support received from healthcare professionals and the community. Understanding parental experience may contribute to the improvement of multidisciplinary syndromic craniofacial management.